Analysis and Design of High Performance Phase Frequency Detector, Charge Pump and Loop Filter Circuits for Phase Locked Loop in Wireless Applications - P.N. Metange; K. B. Khanchandani (Institute of Advanced Engineering and Science, 2016)
This paper presents the analysis and design of high performance phase frequency detector, charge pump and loop filter circuits for phase locked loop in wireless applications. The proposed phase frequency detector (PFD) consumes only 8 µW and utilises small area. Also, at 1.8V voltage supply the maximum operation frequency of the conventional PFD is 500 MHz whereas proposed PFD is 5 GHz. Hence, highly suitable for low power, high speed and low jitter applications. The differential charge pump uses switches using NMOS and the inverter delays for up and down signals do not generate any offset due to its fully symmetric operation. This configuration doubles the range of output voltage compliance compared to single ended charge pump. Differential stage is less sensitive to the leakage current since leakage current behaves as common mode offset with the dual output stages. All the circuits are implemented using cadence 0.18 μm CMOS Process.